Analysis on epidemiological characteristics of food poisoning events in Agadir prefecture, Morocco, from 2015 to 2017 - Bouchriti Youssef (EDP Sciences, 2021)
Food poisoning is a significant public health problem. The aim of this study was to investigate the epidemiological characteristics of food poisoning events in Agadir prefecture in Morocco. Data on food poisoning events was compiled and analyzed from 2015 to 2017. The food poisoning database was created using Excel software, and the data was classified for statistical analysis. In Agadir prefecture, 11 food poisoning events were recorded over the past three years, involving 163 persons and resulting in two deaths. There were 7 and 4 events in the urban and rural areas, respectively. Females were most exposed (67.5%). The annual average morbidity rate was 27.2/100,000, the global lethality rate was 1.3%, and an average of 14.8 persons was involved in a poisoning event. Adolescents make up a quarter of the cases. Most cases occurred in closed communities. The foods involved in these poisoning events were eaten raw. The most common food related with poisoning was meat products. Only six events had samples taken for microbiological testing of the food remaining implicated in the outbreak of these events, and the findings revealed that Salmonella and Escherichia coli were identified in four of the six events, while Candida albicans and total coliforms were detected in two of the six events. Foodborne illness prevention and control should be carried out in closed communities by improving food safety supervision, implementing an effective food poisoning early-warning system, and establishing a surveillance, inspection, and early-warning system for food contaminants and foodborne diseases.